Lease Evaluation. - Bower, Richard S.; Herringer, Frank C.; Williamson, J. Peter (The Accounting Review, 1966)
The purpose of this article is to propose a new method of making the lease-loan choice. This should be of interest to accountants since methods of lease evaluation have important implications for accounting. Much of the disagreement referred to in the preceding paragraph relates to the proper treatment of lease obligations in financial statements. Just as these statements and the judgment of accountants that lies behind them are important determinants of the attitudes of lenders and analysts towards leasing, so also the financial aspects of leasing have implications for proper accounting treatment. The article progresses from a discussion of the nature of leasing to the explanation of a method of lease evaluation that recognizes the nature of leasing. It have fashioned a set of operating instructions that apply this method to lease situations of a particular type. It also applied these instructions in a sample calculation showing also how a computer may be used. There are still questions about estimating the loan rate and the average cost of capital, determining whether the lease choice has a risk effect, applying the method when there is a risk effect, and about the investment decision to take the equipment even in its more advantageous lease or loan form.